Missional worship and social capital formation amid the challenges and opportunities afforded by the Fourth Industrial Revolution : a practical-theological study in the Dutch Reformed Church - La Grange, Marco (Stellenbosch : Stellenbosch University, 2025)
Thesis (PhD)--Stellenbosch University, 2025.